Metabolic Syndrome and Mild Cognitive Impairment - Daylén Pérez Moreno; Vianka Calás Hechavarría; Karel Borroto Martínez; Ángel Miguel Santos Martínez; Raúl Chávez Vega (Revista Finlay)
Foundation: metabolic syndrome is considered a set of cardiovascular risk factors represented by central obesity, dyslipidemia, abnormalities in glucose metabolism and arterial hypertension, closely associated with insulin resistance. Objectives: to characterize metabolic syndrome according to sociodemographic variables and mild cognitive impairment and to determine the association of the elements of said syndrome and mild cognitive impairment in workers at a second-level care center. Method: an analytical and cross-sectional research was carried out in the consultation of workers at a second-level care center in Havana, from May 2022 to May 2023. The universe was made up of 86 workers who were diagnosed with metabolic syndrome. The variables analyzed were: age, sex, smoking habit, personal pathological history, blood pressure. The evaluation of cognitive impairment was done with the application of the mini mental test and the Beck depression inventory. Sociodemographic variables and elements of the metabolic syndrome were described with absolute frequencies and percentages. For the association of risk factors for metabolic syndrome and elements, multivariate analysis was used Results: metabolic syndrome was predominant in non-smoking women aged 51 to 60 years. Metabolic syndrome was not related to mild cognitive impairment, only age was, with statistically significant results. Conclusions: workers over 60 years of age have a higher risk of suffering mild cognitive impairment and there is no association between the elements that make up metabolic syndrome and mild cognitive impairment.